Enhanced passivity of Cr-Fe-Co-Ni-Mo multi-component single-phase face-centred cubic alloys: design, production and corrosion behaviour. (15th May 2022) - Wang, Xueying; Mercier, Dimitri; Danard, Yolaine; Rieger, Thomas; Perrière, Loïc; Laurent-Brocq, Mathilde; Guillot, Ivan; Maurice, Vincent; Marcus, Philippe
Abstract: The vast composition space of the Cr-Fe-Co-Ni-Mo system was explored by massive thermodynamic calculations in order to design and characterize multi-component single-phase fcc alloys optimized in Cr and Mo content and having enhanced passivity. Adding up to 15 at% Mo while retaining the fcc single-phase is possible, which is unprecedented. Cr is confirmed to be a prerequisite to ensure self-protection against corrosion by passivation. Adding Mo up to 10 at% tremendously enhances the resistance to passivity breakdown in Cl - -containing aggressive environment. Newly designed quinary alloys, Cr25 Fe25 Co5 Ni40 Mo5 and Cr15 Fe10 Co5 Ni60 Mo10 (at%), show superior resistance to localized corrosion. Highlights: Fe-Co-Ni-(Cr)-(Mo) multi-component alloys processed based on thermodynamic modelling. Single-phase fcc microstructure characterized by SEM-EDS and XRD. Corrosion resistance investigated and compared to traditional stainless alloys. Cr alloying necessary to ensure self-protection against corrosion by passivation. Mo alloying up to 10 at% enhances resistance to Cl - -induced passivity breakdown.